(untitled) (Islas, 2026)
Introduction: This article examines the presence of glimpses of carnival in the novel La guerra mortal de los sentidos by Roberto Castillo in order to reveal the author’s sardonic stance, his ideas concerning the values of popular culture, language, and relations of subalternity. It also seeks to demonstrate the humor that shapes the novel and to determine whether it embodies a form of subversion and a transgressive vision of Honduran reality. Methods: To identify the ideas associated with carnival in La guerra mortal de los sentidos, a detailed exploration of the novel was conducted using a mixed-methods approach and textual analysis focused on gathering actions, images, episodes, and verbal structures, which were subsequently selected, compared, described, and examined in a manner similar to that employed by Mikhail Bakhtin in his analysis of François Rabelais’s works. Results: The study identified a varied presence of carnival motifs in the novel, including both celebratory elements and those related to language. These glimpses are associated primarily with the first narrative level shaped by the events occurring in El Gual, a space personally connected to the author. Conclusions: The presence of carnival elements in the novel aims at the formulation of a satirical genre linked to humor and utopia, structured around the nature of the guancasco, a form of communal celebration practiced by the Lenca people since ancient times to resolve their differences. However, the ending reveals the unattainability of this aspiration and its ultimately parodic character.